1998
DOI: 10.1111/j.1528-1157.1998.tb01313.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Personality in Adults with Epilepsy

Abstract: Summary:Purpose: This study was undertaken to understand the quality of life, personality, and associated factors in patients with epilepsy.Methods: 117 patients with epilepsy and 84 healthy people were studied and tested using the Social Support Scale, the General Well-being Schedule, the Life-Event Scale, the Behavior Pattern Scale, and the Eysenck Personality QuestionnaireResults: There were no significant differences between the patients with epilepsy and the control group in the Social Support Scale resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…Subjective quality of life and sleep quality is reduced in chronic neurological disorders such as Parkinson's disease [46], migraine [47], epilepsy [48], and narcolepsy [49]. As somatic complaints were increased and sleep and awakening quality as well as quality of life were reduced in MG patients of this study, such an impairment could be confirmed for patients with MG as an example of another chronic neurological disorder.…”
Section: Discussionsupporting
confidence: 57%
“…Subjective quality of life and sleep quality is reduced in chronic neurological disorders such as Parkinson's disease [46], migraine [47], epilepsy [48], and narcolepsy [49]. As somatic complaints were increased and sleep and awakening quality as well as quality of life were reduced in MG patients of this study, such an impairment could be confirmed for patients with MG as an example of another chronic neurological disorder.…”
Section: Discussionsupporting
confidence: 57%
“…Most personality measures included in our review were lengthy; for example, 57 items in the EPI [79], and 88 items in the EPQ [81]. These measures are useful for psychological research, but may be cumbersome for clinical research and application.…”
Section: Discussionmentioning
confidence: 99%
“…In our current study, healthy controls scored better than our nonsurgery epilepsy patients in the functioning domain (especially cognitive functioning) and role‐limitation domain (especially role limitation due to memory) but not in the well‐being domain. Such results are similar to those found in other populations (21–24) and are probably related to multiple socioeconomic and other population‐related factors.…”
Section: Discussionmentioning
confidence: 99%